2015
DOI: 10.1007/s11746-015-2599-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stability and Changes in Chemical Composition of Extra Virgin Olive Oils After Short‐Term Deep‐Frying of French Fries

Abstract: carbonyl compounds, and were highly stable after deepfrying. In addition, oleic acid, tocopherols, and flavor compounds were transferred from EVOO into the French fries.In conclusion, EVOOs were more stable than refined seed oils during short-term deep-frying of French fries and also contributed to enhance the nutritional value, and possibly improve the flavor, of the fries prepared in EVOO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 31 publications
4
48
1
Order By: Relevance
“…Other authors (Akil et al . ) showed a similar result for sunflower oil after frying of French fries. For the two olive oils, the evolution was almost the same.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Other authors (Akil et al . ) showed a similar result for sunflower oil after frying of French fries. For the two olive oils, the evolution was almost the same.…”
Section: Resultssupporting
confidence: 63%
“…For other authors (Akil et al . ), the degradation rate of tocopherols was higher in extra virgin olive oil compared with seed oils. High oleic sunflower oil was richer in this nutritional compound.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Total tocopherol content of Camelina seed oil was reported as 750 mg/kg by Abramovic et al [24], 780 mg/kg by Hrastar et al [10], and 634 mg/kg by Frohlich et al [25]. Camelina seed oil was found to be a better source for tocopherols when compared to some common oils such as canola (492.5 mg/kg) [26], olive (170 mg/kg), soybean (497 mg/kg) [27], rapeseed, sunflower, and sesame oil [28].…”
Section: Effect Of Extraction Parameters On Oil Compositionmentioning
confidence: 98%
“…Tan et al , Ostrowska‐Ligeza et al , and Qi et al used this technique to determine the oxidative stability of olive and other edible oils by means of kinetic parameters that may help to evaluate the oxidative stabilities of oils at increased temperatures. Ostrowska‐Ligeza et al and Qi et al performed the DSC experiments heating at different heating rates, while Tan et al used an isothermal program at different temperatures. Qi et al found good correlations between the kinetics parameters extrapolated from the DSC oxidation curve (i.e., activation energy [ E a ] and reaction rate constant [ k ] with the olive oil compositions [fatty acids and triacylglycerols]), indicating the influence of the oil composition on the thermal oxidation behaviors.…”
Section: Dsc Study Of Olive Oil Oxidation Application On Olive Oilsmentioning
confidence: 99%